Cytological and proteomic analyses of horsetail (Equisetum arvense L.) spore germination - Zhao, Qi; Gao, Jing; Suo, Jinwei; Chen, Sixue; Wang, Tai; Dai, Shaojun (Frontiers in Plant Science, 2015)
Spermatophyte pollen tubes and root hairs have been used as single-cell-type model systems to understand the molecular processes underlying polar growth of plant cells. Horsetail (Equisetum arvense L.) is a perennial herb species in Equisetopsida, which creates separately growing spring and summer stems in its life cycle. The mature chlorophyllous spores produced from spring stems can germinate without dormancy. Here we report the cellular features and protein expression patterns in five stages of horsetail spore germination (mature spores, rehydrated spores, double-celled spores, germinated spores, and spores with protonemal cells). Using 2-DE combined with mass spectrometry, 80 proteins were found to be abundance changed upon spore germination. Among them, proteins involved in photosynthesis, protein turnover, and energy supply were over-represented. Thirteen proteins appeared as proteoforms on the gels, indicating the potential importance of post-translational modification. In addition, the dynamic changes of ascorbate peroxidase, peroxiredoxin, and dehydroascorbate reductase implied that reactive oxygen species homeostasis is critical in regulating cell division and tip-growth. The time course of germination and diverse expression patterns of proteins in photosynthesis, energy supply, lipid and amino acid metabolism indicated that heterotrophic and autotrophic metabolism were necessary in light-dependent germination of the spores. Twenty-six proteins were involved in protein synthesis, folding, and degradation, indicating that protein turnover is vital to spore germination and rhizoid tip-growth. Furthermore, the altered abundance of 14-3-3 protein, small G protein Ran, actin, and caffeoyl-CoA O-methyltransferase revealed that signaling transduction, vesicle trafficking, cytoskeleton dynamics, and cell wall modulation were critical to cell division and polar growth. These findings lay a foundation toward understanding the molecular mechanisms underlying fern spore asymmetric division and rhizoid polar growth.